Banyuwangi: Kota Festival Menuju Destinasi Wisata Indonesia dan Dunia - Purwowibowo Purwowibowo (Journal of Tourism and Creativity, 2020)
Abstract Tourism has become a leading sectors of Banyuwangi Regency to realize the social welfare of the whole communities. This can be seen from the program that was launched by this district to become a major program and important tourist destination in Indonesia, not only for local tourists but also foreign tourists. In fact, the last 5 years the Banyuwangi Regency has made a program that is believed to be an effort to boost tourism activities on a massive scale. The program is a festival, which are a program designed and implemented by all local government officials and supported by the all communities. In 2019, the number of festivals held was 99 activities, one of which is the phenomenal festival that is the 'Gandrung Sewu Festival'. With so many festivals, Banyuwangi and then that city was called and becomes the 'City of Festivals'. Keywords: Banyuwangi, Tourism, Social Welfare, Festival City, Gandrung Sewu